Basaloid squamous cell carcinoma of the larynx: a case report. - (:unkn) unknown (My University, 2005)
Basaloid squamous cell carcinoma (SCC) is a very rare, high grade, and aggressive variant of SCC, with a predilection for the upper aerodigestive system. Treatment should include surgery of the primary tumor and dissection of the cervical lymph nodes, followed by radiotherapy. We present a 50-year-old man with basaloid SCC of the supraglottic larynx, which was initially misdiagnosed as SCC. Supraglottic laryngectomy with bilateral radical neck dissection was performed, and radiotherapy was applied postoperatively. During a follow-up of 26 months, no evidence for recurrence was found. Basaloid SCC should be considered in the differential diagnosis of upper aerodigestive system malignancies because it has a distinct prognostic significance compared to conventional SCC.